Scattering of THz phonons - Wigmore, J; Kozorezov, A; bin Rani, H; Giltrow, M; Kraus, H; Taele, B (2002)
Using heat pulses, we studied the elastic scattering of THz phonons in sapphire and calcium tungstate, two materials of interest as absorbers in composite detectors of particles and photons. For sapphire, we modelled the power dependences of specularly reflected and bulk scattered phonons, whilst for calcium tungstate the transmitted diffusive signal was measured. In both materials, the measured rate was consistent with Rayleigh scattering by isotopes, of oxygen in Al2O3 and of tungsten in CaWO4. In addition, strongly non-linear effects were observed in CaWO4. (C) 2002 Elsevier Science B.V. All rights reserved.